Scoring System for Lesions Induced by Different Strains of Infectious Bursal Disease Virus in Chicken - Hussein , Elawad A.; Hair-Bejo, M.; Omar, A.R.; Liew, Pit S.; Saeed, Mohammed Ibrahim; Arshad, Siti S.; Awad, Elmutaz A.; Aini, I. (International Journal of Poultry Science, 2020)
Background and Objective: There are 3 pathogenic strains of infectious bursal disease virus (IBDV), which are classical, variant and very virulent strains. The objective of this study was to design a scoring system for lesions induced by different strains of infectious bursal disease virus in chicken. Materials and Methods: Three experiments were conducted. In experiments 1 and 2, chickens were divided into infected and control groups. Infected groups of experiments 1 and 2 consisted of 15 and 24 specific pathogen-free (SPF) chickens, respectively. Infection was induced by oral administration of 107.5 50% EID50/0.1 mL of very virulent IBDV (vvIBDV). Infected chickens in experiment 1 were euthanised by cervical dislocation on days 1, 2, 3, 4 and 5 post-inoculation (pi). Infected chickens in experiment 2 were euthanised at hours (h) 2, 4, 6, 12 and days 1, 2, 4 and 6 pi. Control groups in experiments 1 and 2 consisted of 6 and 15 SPF chickens, respectively. Chickens of the control group in experiment 1 were euthanised on days 1 and 5 pi, whereas control group chickens in experiment 2 were euthanised on days 0, 1, 2, 4 and 6 pi. Then, 20 SPF chickens, in experiment 3, were divided into three groups; in the first group, 10 SPF chickens were infected with vvIBDV, in the second group, 5 SPF chickens were infected with classical IBDV (caIBDV) (103.0 EID50/0.1 mL) and the third group of chicken was kept as a control group without infection. Five chickens from first group, five chickens of second group and five chicken of the third group were euthanised on day 4 pi. Another 5 chickens from first group were euthanized on day 7 pi. In all previous experiments, tissues of bursa of Fabricius, caecal tonsil, liver, kidney, spleen, junction of proventriculus and gizzard, intestine, muscle and thymus were collected, fixed in 10% buffered formalin, embedded in paraffin and sectioned. HS staining was applied. Results: When the strain of the virus was vvIBDV, the scoring was always greater in comparison with the strain caIBDV. The lesions induced in the bursa of Fabricius by vvIBDV strain, when the infection was chronic, were determined. Conclusion: A scoring system for the lesions induced by different strains of IBDV in 9 different tissues was expected to be beneficial in the field of histopathology.